In vivo efficacy proof of concept of a large-size bioprinted dermo-epidermal substitute for permanent wound coverage - Abellan Lopez, Maxime; Hutter, Laurence; Pagin, Etienne; Vélier, Mélanie; Véran, Julie; Giraudo, Laurent; Dumoulin, Chloe; Arnaud, Laurent; Macagno, Nicolas; Appay, Romain; Daniel, Laurent; Guillet, Benjamin; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction Autologous split thickness skin graft (STSG) is a standard treatment for coverage of full thickness skin defects. However, this technique has two major drawbacks: use of a general anesthesia for skin harvesting and scar sequelae on the donor site. In order to reduce morbidity associated with STSG harvesting, researchers have developed autologous dermo-epidermal substitutes (DES) using cell culture, tissue engineering and more recently bioprinting approaches. This study assessed the manufacturing reliability and the in vivo efficacy of a large size Good Manufacturing Practice (GMP) compatible bio-printed human DES, named Poieskin®, for acute wound healing treatment. Methods Two batches (40 cm2 each) of Poieskin® were produced and their reliability and homogeneity were assessed using a histological scoring. Immunosuppressed mice received either samples of Poieskin® (n=8) or Human STSG (n=8) immediately after longitudinal acute full-thickness excision of 1x1.5cm size, applied on the skeletal muscle plane. Engraftment rate was assessed on standardized photographs at 16 days-followup. Moreover, wound contraction, superficial vascularization and local inflammation were evaluated via standardized photographs, LASER-Doppler imaging and PET imaging, respectively. Histological analysis was finally performed after euthanasia. Results Histological scoring reached 75±8% and 73±12% respectively, displaying a robust and homogeneous construct. Engraftment was comparable for both groups: 91.8% (SD=0.1152) for Poieskin® group versus 100% (SD=0) for Human STSG. We did not record differences neither in graft perfusion, PET imaging nor histological scoring at 16 days. Conclusion Poieskin® presents consistent bio-engineering manufacturing characteristics to treat full thickness cutaneous defects as an alternative to STSG in clinical applications. Manufacturing of Poieskin® is reliable and homogeneous leading to a clinically satisfying rate of graft take compared to the reference Human STSG in a mouse model. These results encourage the use of Poieskin® in phase I clinical trials as its manufacturing procedure is compatible with pharmaceutical guidelines.